2017
DOI: 10.1111/fwb.12921
|View full text |Cite
|
Sign up to set email alerts
|

Allochthonous and autochthonous carbon flows in food webs of tropical forest streams

Abstract: The River Continuum Concept (RCC) assumes that autochthonous primary production in forest streams is limited by light and is insufficient to sustain secondary production by consumers; they must therefore depend on allochthonous carbon from the surrounding forest. Recent studies have, however, questioned the importance of allochthonous carbon in stream food webs. There is a growing body of evidence using stable‐isotope techniques that demonstrate the importance of algae (autochthonous production) in the food we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 70 publications
0
38
0
6
Order By: Relevance
“…The grouping of dietary items, into the higher and lower aquatic resources and terrestrial resources, can be applied to examine larger‐scale ecological patterns in resource use (Neres‐Lima et al., ; Phillips, Newsome, & Gregg, ). We expected terrestrial resources to be more important at woodland sites as leaf litter dominates the nutrient input of many forested streams, and the canopy reduces light availability for growth of autochthonous primary producers (Neres‐Lima et al., ; Rounick, Winterbourn, & Lyon, ). However, besides leaf litter, the terrestrial resources also included terrestrial plants (mainly grasses and riparian herbaceous plants), which largely contributed to the consumers’ diet at urban and agricultural sites.…”
Section: Discussionmentioning
confidence: 99%
“…The grouping of dietary items, into the higher and lower aquatic resources and terrestrial resources, can be applied to examine larger‐scale ecological patterns in resource use (Neres‐Lima et al., ; Phillips, Newsome, & Gregg, ). We expected terrestrial resources to be more important at woodland sites as leaf litter dominates the nutrient input of many forested streams, and the canopy reduces light availability for growth of autochthonous primary producers (Neres‐Lima et al., ; Rounick, Winterbourn, & Lyon, ). However, besides leaf litter, the terrestrial resources also included terrestrial plants (mainly grasses and riparian herbaceous plants), which largely contributed to the consumers’ diet at urban and agricultural sites.…”
Section: Discussionmentioning
confidence: 99%
“…, but see Neres‐Lima et al. ). Despite publications indicating some differences between ecosystem processes in tropical streams from temperate, we do not know whether ecosystem processes in tropical and subtropical forested streams scale differently from studied temperate streams, in spite of the global importance of tropical streams (Dodds et al.…”
Section: Introductionmentioning
confidence: 98%
“…However, this view continues to be challenged. For example, Brito, Moulton, Souza, and Bunn () and Neres‐Lima et al () found that the food web of an Atlantic Forest stream was predominately based on autochthonous resources, whereas Neres‐lima et al () found the food web was predominately based on allochthonous resources in other tropical streams. Terrestrial insects have also been reported to play an important role in the diet of fish in some tropical forested streams (Casatti, ; Rezende & Mazzoni, ).…”
Section: Introductionmentioning
confidence: 99%